TACTICS OF MODERN MINIMALLY INVASIVE INTERVENTIONS IN SURGICAL TREATMENT OF ACUTE PANCREATITIS - Seliyan Harihara Sudhan, Yunusova Guzal Fayzullaevna (Research Focus International Scientific Journal, 2025)
Minimally invasive interventions are more effective than open surgery in the treatment of aseptic severe acute pancreatitis. This was shown by analysing data obtained from the treatment of 182 patients with severe acute pan- creatitis. The reduction in the incidence of mortality was 6.2% and 17.2%, respectively. Since the mortality rate was 19.8% in infected pancreonecrosis, the use of minimally invasive procedures was preferred over open surgery.